Erosion of nanostructured tungsten by laser ablation, sputtering and arcing. (August 2017) - Hwangbo, Dogyun; Kawaguchi, Shota; Kajita, Shin; Ohno, Noriyasu
Highlights: Sputtering was dominant by impurities below the helium sputtering threshold. Reduction in sputtering by nanostructure surface was re-confirmed by mass loss measurement. Erosion per unit time by arcing increased with increasing the arc current. Erosion per unit charge amount did not have a relation with the arc current. Abstract: Mass loss of nanostructured tungsten, which was formed by helium plasma irradiation, due to laser ablation, sputtering, and arcing was investigated. Below the helium sputtering energy threshold (<117 eV), sputtering by impurity gases such as nitrogen and oxygen was dominant. Sputtering yield became closer to theoretical value with increasing the incident ion energy, and sputtering by helium ions became the major contribution when the energy was >200 eV. Reduction in sputtering on nanostructured surface was observed. Arcing was initiated using laser pulses, and the erosion rate by arcing was measured. The erosion rate increased with arc current, while the erosion per Coulomb was not affected by arc current.